A Study of Thermal Analysis of KAONICS - Jina Kang; Sungho Lee; Ho Jin; Soojong Pak; Bongkon Moon; Sang-Ho Kim; Jang-Hyun Park (Journal of Astronomy and Space Sciences, 2004)
It is very important to eliminate thermal background radiation for the near infrared camera system such as KAONICS (KAO Near Infrared Camera System). Thermal background radiations which come from window and cryostat wall influence IR detector and decrease IR system performance. Therefore the cold box which contains optics and detector housing must be cooled down to eliminate thermal background radiation. We carried out quantitative analysis to determine internal cooling temperature to reduce thermal noise in the J, H, Ks, and L bandpass. Additionally, we estimated the incoming heat load and then chose the cryocooler adequate to KAONICS's requirements. The cooling time and the final cooling temperature of the cold box were calculated. These results were also implemented to the system design.